The critical space - Singh, Manjit Inder (National Publ. House, 2005)
Chiefly on English novels by 20th century Indic authors.
Chiefly on English novels by 20th century Indic authors.
Keywords: Aufsatzsammlung; Indic fiction (English); East Indian diaspora in literature; Nationalism in literature; Nation; Literatur